Measuring bias in aerial surveys due to dispersion of animals - Newsome, A.E.; Dudzinski, M.L.; Low, W.A. (International Livestock Centre for Africa, 1981)
Examines possible bias in aerial surveys of animals due to dispersion, using extensive data on cattle; and describes ways to adjust estimates.